2018
DOI: 10.1186/s12948-018-0086-7
|View full text |Cite
|
Sign up to set email alerts
|

Role of genetic variations of chitinase 3-like 1 in bronchial asthmatic patients

Abstract: BackgroundSingle nucleotide polymorphisms (SNPs) in chitinase 3-like 1 (CHI3L1) are associated with bronchial severity and pulmonary function. CHI3L1 proteins are involved in both innate and adaptive immune responses; however, to date, the correlation of these SNPs and their age of onset of bronchial asthma has not been demonstrated.MethodsTo address the role of these genetic variations, 390 patients with well-controlled bronchial asthma and living in Japan were recruited, genotyped, and had a pulmonary functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…The same associations were replicated in Japanese asthmatics, in whom the CHI3L1 SNP rs12141494 AA genotype was associated with decreased FEV1% 33. Furthermore, the CHI3L1 SNP rs12141494 A allele was associated with higher levels of YKL-40 in the asthmatic airway as measured in both sputum ( P ≤ 0.05)32 and bronchoalveolar lavage (BAL) ( P < 0.05, 770.8 pg/mL for AA vs. 179.3 pg/mL for GG) 33. These findings suggested that CHI3L1 genetic polymorphism modulated expression of YKL-40 in the airway and contributed to lung function in asthma.…”
Section: Genes Regulating Decline In Lung Function And/or Airway Remomentioning
confidence: 61%
See 1 more Smart Citation
“…The same associations were replicated in Japanese asthmatics, in whom the CHI3L1 SNP rs12141494 AA genotype was associated with decreased FEV1% 33. Furthermore, the CHI3L1 SNP rs12141494 A allele was associated with higher levels of YKL-40 in the asthmatic airway as measured in both sputum ( P ≤ 0.05)32 and bronchoalveolar lavage (BAL) ( P < 0.05, 770.8 pg/mL for AA vs. 179.3 pg/mL for GG) 33. These findings suggested that CHI3L1 genetic polymorphism modulated expression of YKL-40 in the airway and contributed to lung function in asthma.…”
Section: Genes Regulating Decline In Lung Function And/or Airway Remomentioning
confidence: 61%
“…The CHI3L1 SNP rs12141494 A allele was significantly associated with higher serum YKL-40 levels and decreased post-bronchodilator FEV1% in the Severe Asthma Research Program cohort 32. The same associations were replicated in Japanese asthmatics, in whom the CHI3L1 SNP rs12141494 AA genotype was associated with decreased FEV1% 33. Furthermore, the CHI3L1 SNP rs12141494 A allele was associated with higher levels of YKL-40 in the asthmatic airway as measured in both sputum ( P ≤ 0.05)32 and bronchoalveolar lavage (BAL) ( P < 0.05, 770.8 pg/mL for AA vs. 179.3 pg/mL for GG) 33.…”
Section: Genes Regulating Decline In Lung Function And/or Airway Remomentioning
confidence: 63%
“…Chitinase 3-like-1 (Chi3L1), also called a breast regression protein 39 (BRP-39) in mouse and YKL-40 in human, is known as a secreted glycoprotein and prototypic mammalian chitinase like protein [11,12]. Increased expression of Chi3L1 protein and mRNA have been shown in various disease models and states including rheumatoid arthritis schizophrenics, inflammatory bowel disease, chronic obstructive pulmonary disease, asthma, diabetes, and atherosclerosis [13][14][15][16][17][18][19], Especially, Chi3L1 expression has been found in a variety of cancer cells such as breast, lung, prostate, colon, rectum, ovary, kidney, breast, glioblastomas, and malignant melanoma [20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Among the most studied SNPs in the CHI3L1 gene such as rs1538372 or rs10399931, we decided to choose -131 C→G (rs4950928) SNP as it is located in the promoter region of CHI3L1 gene. Besides, there was a growing number of papers reporting its association with asthma in different populations [28][29][30][31][32][33]. These papers are summarized and presented in Table 3.…”
Section: Discussionmentioning
confidence: 99%